Emerging endocrine disruptors in two edible fish from the Persian Gulf: Occurrence, congener profile, and human health risk assessment. (May 2021) - Akhbarizadeh, Razegheh; Russo, Giacomo; Rossi, Sergio; Golianova, Katarina; Moore, Farid; Guida, Marco; De Falco, Maria; Grumetto, Lucia
Abstract: The occurrence of endocrine disrupting chemicals (EDCs) has been determined in two widely consumed fish species from Persian Gulf i.e., Epinephelus coioides and Platycephalus indicus by applying a validated analytical for the simultaneous detection of fourteen EDCs. The concentrations of all detected EDCs were greater in the liver than in the muscle (except for bisphenol A in P. indicus ), suggesting a prolonged exposure of the fishes to these pollutants in the Persian Gulf. Specifically, the results showed that di (2-ethylhexyl) phthalate (DEHP) was the compound detected most frequently and at the highest concentration in both species. DEHP levels in ranged from 6.68 to 297.48 μg g-dw −1 and from 13.32 to 350.52 μg g-dw −1, in muscle and in liver, respectively. A risk assessment study was conducted, and demonstrated that consuming two fish based- meals per week may result in a moderate risk especially for vulnerable population groups. Graphical abstract: Unlabelled Image Highlights: Occurrence of 14 EDCs was investigated in two fish species from the Persian Gulf. DEHP, BPA, BPAF, and BADGE showed a frequency detection above 74%. The level of almost all detected EDCs was higher in liver than muscle. Possible co-exposure to EDCs may threat the human health via fish consumption. Consumption of two fish based- meals per week, may result in a moderate health risk.